The dependence of the ectopic electrical activity of the heart on the excess body weight in patients with essential hypertension in combination with ischemic heart disease (according to the daily ECG monitoring) - V. V. Syvolap; L. O. Kurilets; V. A. Matsalaeva; N. Ye. Dobrovolska (Patologìâ)
Вackground. Obesity, hypertension and myocardial ischemia due to coronary atherosclerosis are the most common combination of pathological conditions. Arrhythmias (except for atrial fibrillation) in patients with obesity and hypertension in combination with ischemic heart disease are neglected.